The psychometric properties of the Persian version of the moral injury symptoms scale-health care professionals version - Malakoutikhah, Alireza; Zakeri, Mohammad Ali; Koenig, Harold G.; Dehghan, Mahlagha (Frontiers in Psychology, 2022)
Background: Health care professionals face a number of problems during crises, such as the COVID-19. Studies addressed the prevalence of moral injury among healthcare professionals during the COVID-19 outbreak. Lack of a valid standard of moral injury among health care professionals is one of the factors that has made it difficult to identify and treat this complication. This study aimed to evaluate the psychometric properties of the Moral Injury Symptoms Scale-Health Care Professionals (MISS-HP) among health care professionals in Iran. Methods: This study was conducted to evaluate the validity and reliability of the MISS-HP. The sample included 455 healthcare professionals working in three teaching hospitals in Kerman, who were in direct contact with patients. In this study, face validity, content validity, construct validity (structural and convergent), and internal reliability of the MISS-HP were evaluated. Demographic information questionnaire, the Moral Injury Symptoms Scale-HealthCare Professionals (MISS-HP), General Health Questionnaire (GHQ), and Impact of Event Scale (IES) were administered to study participants. Results: The MISS-HP was evaluated using translation-back translation technique. The content validity index of the items (I-CVI) and the scale (S-CVI) were 0.9 and 0.99, respectively. Exploratory factor analysis showed a three-factor structure in the MISS-HP that explained 57.49% of the variance. Confirmatory factor analysis indices were acceptable. The cut-off point of the questionnaire was 36.5. There was a positive and moderate correlation between the Persian version of MISS-HP, GHQ (r = 0.34), and IES-R (r = 0.40). The Cronbach's alpha coefficient of the Persian version of MISS-HP was 0.70. Conclusion: This study found that the MISS-HP is a concise, comprehensive, valid and reliable scale for assessing moral injury among health care professionals in clinical or research settings. This scale will be helpful for managers and researchers to identify and plan health policies and improve the psychological state of health care professionals.